If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.75 = 2x + 0.15 Reorder the terms: 2.75 = 0.15 + 2x Solving 2.75 = 0.15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2.75 + -2x = 0.15 + 2x + -2x Combine like terms: 2x + -2x = 0 2.75 + -2x = 0.15 + 0 2.75 + -2x = 0.15 Add '-2.75' to each side of the equation. 2.75 + -2.75 + -2x = 0.15 + -2.75 Combine like terms: 2.75 + -2.75 = 0.00 0.00 + -2x = 0.15 + -2.75 -2x = 0.15 + -2.75 Combine like terms: 0.15 + -2.75 = -2.6 -2x = -2.6 Divide each side by '-2'. x = 1.3 Simplifying x = 1.3
| 8y-2y=132 | | 0.10(y-4)+0.08y=0.02y-0.03(40) | | 9x=7y+2 | | 3x+4y=-36graph | | k+8=4k-1 | | 4(y+6)=16 | | 3b-9+8b=11 | | f(x)=-x^2+5 | | 4z-8-2+2=0 | | 2f(1)=3(1+1)(1+1)-1 | | 4x+9=5x+21 | | 3x/4-1/2=7 | | 13x+5/3-12x=14/15 | | 4(2x-2)=3x+22 | | 6(d+15)=120 | | 9x^3+36x=0 | | 7n+2n=9 | | 5x-8=x(1.8) | | 3/4d=75 | | 2x-6(+6)=10(+6) | | 6(1.3x-3)=2.6x-5 | | 8t+3=11 | | (3/2)(2x+2)-(3/5)(5x+5)=(6/5)(10x+6) | | 2f(1)=3(2+1)(2+1)-1 | | 5+4(2x-1)=3(x+1)+5x | | 13x+5/3-12x= | | -3x+2=6x+56 | | a^3+7a^2-8a=0 | | 40=5/8c | | 13z+4z-13z+2z=10 | | (x+7)/12=11 | | 3x-16+7x=-76 |